The pH of Enceladus' ocean. (1st August 2015) - Glein, Christopher R.; Baross, John A.; Waite, J. Hunter
Abstract: Saturn's moon, Enceladus, is a geologically active waterworld. The prevailing paradigm is that there is a subsurface ocean that erupts to the surface, which leads to the formation of a plume of vapor and ice above the south polar region. The chemistry of the ocean is just beginning to be understood, but is of profound geochemical and astrobiological interest. Here, we determine the pH of the ocean using a thermodynamic model of carbonate speciation. Observational data from the Cassini spacecraft are used to make a chemical model of ocean water on Enceladus. The model suggests that Enceladus' ocean is a Na–Cl–CO3 solution with an alkaline pH of ∼11–12. The dominance of aqueous NaCl is a feature that Enceladus' ocean shares with terrestrial seawater, but the ubiquity of dissolved Na2 CO3 suggests that soda lakes are more analogous to the Enceladus ocean. The high pH implies that the hydroxide ion should be relatively abundant, while divalent metals should be present at low concentrations owing to buffering by carbonates and phyllosilicates on the ocean floor. Carboxyl groups in dissolved organic species would be negatively charged, while amino groups would exist predominately in the neutral form. Knowledge of the pH improves our understanding of geochemical processes in Enceladus' ocean. The high pH is interpreted to be a key consequence of serpentinization of chondritic rock, as predicted by prior geochemical reaction path models; although degassing of CO2 from the ocean may also play a role depending on the efficiency of mixing processes in the ocean. Serpentinization leads to the generation of H2, a geochemical fuel that can support both abiotic and biological synthesis of organic molecules such as those that have been detected in Enceladus' plume. Serpentinization and H2 generation should have occurred on Enceladus, like on the parent bodies of aqueously altered meteorites; but it is unknown whether these critical processes are still taking place, or if Enceladus' rocky core has been completely altered by past hydrothermal activity. The presence of native H2 in the plume would provide strong evidence for contemporary aqueous alteration that replenishes this source of energy for possible life. The high pH also suggests that the delivery of strong oxidants from the surface to the ocean has not been significant (otherwise, sulfuric acid would be produced), which would be consistent with geophysical models of episodic resurfacing activity on Enceladus. This paper represents an expansion of chemical oceanography to an "ocean planet" beyond Earth.